Cancer burden in Europe: a systematic analysis of the GLOBOCAN database (2022) - Mohammed Elmadani; Peter Onchuru Mokaya; Ahmed A. A. Omer; Evans Kasmai Kiptulon; Simon Klara; Mate Orsolya (BMC Cancer)
Abstract Background Cancer remains a significant public health challenge in Europe, with substantial regional disparities in incidence, mortality, and access to healthcare. This study analyses cancer patterns across Eastern, Northern, Southern, and Western Europe in 2022, highlighting key public health implications and gaps in prevention and treatment. Methods Using data from GLOBOCAN 2022, this study assessed total new cancer cases, age-standardized incidence and mortality rates (ASRs) per 100,000, and cumulative cancer risk at age 75. The top three cancers by sex and region were also analysed to identify trends and disparities. Results In 2022, Europe recorded 4,471,422 new cancer cases (ASR 280 per 100,000), with a cumulative risk of 27.9% by age 75. Males accounted for 2,359,303 cases (ASR 319.6, cumulative risk 31.9%), while females had 2,112,119 cases (ASR 253.4, cumulative risk 24.7%). Northern and Western Europe had the highest incidence rates, with Denmark leading at 374.7 per 100,000 (cumulative risk 34.9%), likely due to advanced screening and healthcare. Conversely, Eastern Europe had the highest mortality, with 1,091,871 deaths (ASR 135.3), reflecting late diagnoses and limited access of treatment. Hungary exhibited the highest mortality rate (ASR 143.7, cumulative risk 15.8%), followed by Poland (ASR 133.1). Prostate and breast cancers were the most common in males and females, respectively. Lung cancer, despite a lower incidence (ASR 24.7), had the highest mortality (ASR 17.7), while pancreatic cancer showed high fatality (ASR 6.3, mortality ASR 5.6). Thyroid cancer had a relatively high incidence (ASR 7.5) but low mortality (ASR 0.21). Conclusions Significant regional disparities in cancer burden underscore the need for targeted public health strategies. Expanding cancer screening programs, strengthening smoking cessation and HPV vaccination efforts, and improving healthcare accessibility particularly in Eastern Europe are critical to reducing mortality and enhancing early detection. Differences in mortality-to-incidence ratios also highlight the role of healthcare infrastructure and timely interventions. Future research should explore the socioeconomic and environmental determinants driving these disparities to inform evidence-based cancer control policies across Europe.